DIFFERENCE OF PERCEPTION OF THE QUALITY OF LIFE OF ADULTS PRACTITIONERS AND NON-PRACTITIONERS OF PHYSICAL ACTIVITY (Fiep Bulletin - online, 2013)
The World Health Organization (who) defines quality of life as the individual's perception of their position in life, in thecontext of culture and value system in which he lives, considering your goals, expectations, standards and concerns. (BRAZIL,1994). The regular practice of physical activity covers benefits in addition to the physical aspect. Studies have discussed anddemonstrated the importance of regular practice of physical activity as a means of preventing disease associated with sedentarylifestyle. (NOCE et al, 2009). The objective of this study was to investigate and differentiate the perception of quality of life ofregular physical activity for health promotion and sedentary adults of both sexes, at the age of 21 years on, residents of Rio deJaneiro in areas north and West. The General physical activity index of the Group was predominantly active (± 46.43) theWHOQOL-BREF questionnaire used evaluated the perception of quality of life of individuals, where the average of the scoresobtained in each domain of the quality of life is presented in Figure 6, where you can see that the variance between thepsychological areas averaging 61.9 and environment with ± ± 63 was minimal in relation to both and to the other domains. Theresults obtained suggest that the rate of physical activity in relation to the level of perception of quality of life is not a determiningfactor in the increased values of areas and varies according to the population of each region. The relationship of the results of thestudy does not rule out the relevance of the practice of everyday life activity of an individual, but stresses the importance of a morespecific interference by government authorities, through greater investments in education and infrastructure of each region andof health care workers.
Keywords: quality of life; IPAQ; WHOQOL-BREF